Madrasah Head Leadership Strategy in Developing the Learning Process in the Era of Disruption - Moh. Holili; Wahidmurni Wahidmurni; Indah Aminatuz Zuhriyah; Bima Fandi Asy’arie; Nadiah Abidin (SYAMIL: Journal of Islamic Education, 2024)
The research aims to identify the leadership model of madrasah heads in formulating learning policies and then to analyze implementation in developing learning processes in the era of disruption. This research design is multisite, using a qualitative approach. The focus of this research was carried out at MA Al-Mukhlisin Blega and SMA Ash-Shahihiyah Blega, Bangkalan Regency, East Java. Then the participants from the total number of informants were 14 informants, including school and madrasa principals, curriculum heads, Islamic teachers, and students. The findings of the discussion in this article are obtained. First, there are differences in the leadership style models of the two schools. Where there is a democratic leadership spirit, and the implementation of management is bottom-up. Then, the leader's authoritarian, paternalistic attitude or top-down management. Second, there are two learning models: blended and hybrid. The educational staff uses applications such as (Google Classroom, Kahoot, Microsoft Teams, LMS Canvas, Quora, and Lectora). Thus, this article provides a deeper understanding of the leadership model of madrasas and school principals in formulating learning policies in the era of disruption so that it can be used as a reference in developing adaptive educational strategies. In addition, analysis of policy implementation provides a real picture of the effectiveness of learning practices in the field, which contributes to improving the quality of education and strengthening the madrasa management system in an era of technological change.